Student’s Perception of their Learning Approach and Relationship with Level of Engagement in Science Lessons - Nasir MAHMOOD (Ankara Üniversitesi Eğitim Bilimleri Fakültesi Dergisi)
The study focused on finding the relationship between students‟ proximity with constructivist principles of learning and their engagement in science lessons. Constructivist Learning Scale (CLS) by Mahmood (2004) was used to distribute students in two groups on the basis of their proximity to using constructivist learning approach for their science learning. In addition, a self-report engagement questionnaire comprising of six questions was used to record students‟ assessment of their own engagement at the end of each lesson while learning about “solution”. The comparison of two groups showed that students exercising greater proximity to the constructivist approach toward learning had more interest, collaborated well and exceedingly involved in discussion with classfellow/teachers. Moreover, they were also more composed and meaningful in their style of writing as far as conciseness and communicability of language was concerned, as compared to students with less constructivist approach to learning